Development of Secured Authentication Contract Communication Network Protocol for IoT Environment - Al Momani, Mahdi Mohammad Abdullah; Puttaswamy, P S (2022 Fourth International Conference on Emerging Research in Electronics, Computer Science and Technology (ICERECT), 2022)
Internet of Things (IoT) is a subject of great interest and is the current technology. For the last few years, IoT application has increased many folds. In addition, systems security has been a wonderful field for research activities. The mutual authentication between the IoT devices and Users of the IoT Environment is a significant part of secure IoT systems. At present the widely used authentication mechanisms are Single password based and are likely vulnerable to side-channel and dictionary attacks. This paper introduces a multi-key-based mutual authentication mechanism to provide a contract for secure authentication and communication between the IoT devices and Users of the IoT Environment. It also deals with publish-subscribe-based Message Queuing Telemetry Transport (MQTT) protocol is used for secure communication, which is bandwidth-efficient and uses a small amount of battery power. The blockchain technology is used in the present work to store data helps to bring trust and transparency to the developed model. The implementation of this entire methodology, the authors has created a prototype using Node MCU ESP8266 and Arduino IDE IoT platform for IoT Environment. To have secured communication via the cloud has been designed for the client to control IoT devices, and the same will be stored using blockchain technology for future data validation. The Node MCU ESP8266 IoT platform used in the present work makes effective and fast IoT applications.